ANALISA PETROFISIKA SUMUR PEMBORAN DAN INTERPRETASI SEISMIK UNTUK IDENTIFIKASI RESERVOAR DAN PERHITUNGAN VOLUMETRIK CADANGAN MINYAK BUMI PADA LAPANGAN M FORMASI TALANG AKAR CEKUNGAN JAWA BARAT UTARA - , REZA HARI SETIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Petrophysical analysis and seismic interpretation has been carried out to identify and calculate the volumetric of oil reserves on field âMâ, the field of ASSET 3 PT. Pertamina EPâs work area in North West Java Basin. The petrophysical analysis was performed to determine the rocks physical property (i.e. shale volume, porosity, water saturation, permeability) and to identify reservoir with its hydrocarbon content. Seismic Interpretation was performed to obtain reservoir volume from its geometry. The final result of this research is total oil reserves volume on a reservoir. Shale volume calculated using Clavier non-linear method, effective porosity calculated using neutron/density Bateman-Konen method, water saturation calculated using Modified Simandoux method, and permeability using Coates FFI method. Total oil reserves calculated using volumetric method with the petrophysical and seismic interpretation result as parameter input. From the analysis that focused on Talang Akar Formation, North West Java Basin can be obtained three reservoirs